Identification of porcine PARP11 as a restricted factor for pseudorabies virus - Chunyun Qi; Dehua Zhao; Xi Wang; Lanxin Hu; Yao Wang; Heyong Wu; Feng Li; Jian Zhou; Tianyi Zhang; Aosi Qi; Yuran Huo; Qiuse Tu; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionPRV infection in swine can cause devastating disease and pose a potential threat to humans. Advancing the interplay between PRV and host is essential to elucidate the pathogenic mechanism of PRV and identify novel anti-PRV targets.MethodsPARP11-KO PK-15 cells were firstly constructed by CRISPR/Cas9 technology. Next, the effect of PARP11-KO on PRV infection was determined by RT-qPCR, TCID50 assay, RNA-seq, and western blot.Results and discussionIn this study, we identified PARP11 as a host factor that can significantly affect PRV infection. Inhibition of PARP11 and knockout of PARP11 can significantly promoted PRV infection. Subsequently, we further found that PARP11 knockout upregulated the transcription of NXF1 and CRM1, resulting in enhanced transcription of viral genes. Furthermore, we also found that PARP11 knockout could activate the autophagy pathway and suppress the mTOR pathway during PRV infection. These findings could provide insight into the mechanism in which PARP11 participated during PRV infection and offer a potential target to develop anti-PRV therapies.